(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
English as a Foreign Language (TOEFL) is a standardized test that determines the test taker’s level of English. TOEFL certificate is valid for 2 years. It was introduced for the first time in 1964. Since then, more than 20 million people have submitted it. Also, TOEFL is one of the two main tests that determine the level of English proficiency in the world, the other being IELTS